GENERATION Z FACING THE CLIMATE CRISIS: THE LINK BETWEEN SELF-EFFICACY AND CLIMATE CHANGE ANXIETY - Nafilah, Rifdah Shafa; Jaro’ah, Siti (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2025)
Climate change has become a global issue with not only environmental but also psychological impacts, particularly in the form of climate change anxiety. This anxiety is often experienced by young people, including Generation Z, who are increasingly aware of the threats posed by the climate crisis. On the other hand, self-efficacy is considered an important psychological resource that helps individuals manage stress and challenges. This study aims to examine the relationship between self-efficacy and climate change anxiety among Generation Z. The research employed a quantitative correlational design with 413 respondents selected through accidental sampling. Data were collected using a self-efficacy scale and a climate change anxiety scale, and analyzed through Pearson correlation, and Spearman’s rho. The results showed that self-efficacy did not significantly correlate with climate change anxiety (p > 0.05), indicating that high or low self-efficacy does not directly affect the level of anxiety about climate change. These findings suggest that climate change anxiety is more strongly influenced by other factors, such as exposure to information, risk perception, or future-oriented distress. The implication of this study is that interventions to address climate change anxiety should not rely solely on strengthening self-efficacy, but also consider enhancing social support, environmental literacy, and positive emotions such as hope.